Is Brain Dynamics Preserved in the EEG After Automated Artifact Removal? A Validation of the Fingerprint Method and the Automatic Removal of Cardiac Interference Approach Based on Microstate Analysis - Tamburro, Gabriella; Croce, Pierpaolo; Zappasodi, Filippo; Comani, Silvia (Frontiers in Neuroscience, 2021)
The assessment of a method for removing artefacts from EEG datasets often disregard verifying that global brain dynamics is preserved. In this study, we verified that the recently introduced optimized Fingerprint Method and ARCI approach not only remove physiological artefacts from EEG recordings but also preserve global brain dynamics, as assessed with a new approach based on microstate analysis. We recorded EEG activity with a high-resolution EEG system during two resting state conditions (eyes open, 25 volunteers, and eyes closed, 26 volunteers) known to exhibit different brain dynamics. After signal decomposition by Independent Component Analysis (ICA), the independent components (ICs) related to eyeblinks, eye movements, myogenic interference and cardiac electro-mechanical activity were identified with the Optimized Fingerprint Method and ARCI approach, and statistically compared with the outcome of the expert classification of the ICs by visual inspection. Brain dynamics in two different groups of denoised EEG signals, reconstructed after having removed the artefactual ICs identified by either visual inspection or the automated methods, was assessed by calculating microstate topographies, microstate metrics (duration, occurrence and coverage) and directional predominance (based on transition probabilities). No statistically significant differences between the expert and the automated classification of the artefactual ICs were found (p > 0.05). Cronbach’s α values assessed high test-retest reliability of microstate parameters for EEG datasets denoised by automated procedure. The total EEG signal variance explained by the sets of global microstate templates was about 80% for all denoised EEG datasets, with no significant differences between groups. For the differently denoised EEG datasets in the two recording conditions, we found that the global microstate templates and the sequences of global microstates were very similar (p < 0.01). Descriptive statistics and Cronbach’s α of microstate metrics highlighted no significant differences and excellent consistency between groups (p > 0.5). These results confirm the ability of the Optimized Fingerprint Method and the ARCI approach to effectively remove physiological artefacts from EEG recordings while preserving global brain dynamics. They also suggest that microstate analysis could represent a novel approach for assessing the ability of an EEG denoising method to remove artefacts without altering brain dynamics.